Preparation method of DNA hydrogel with programmable mechanical strength

By adjusting the molar ratio of the catalytic initiation chain to the DNA monomer building block, DNA hydrogels were prepared under isothermal conditions. This solved the problem of multiple parameter changes when regulating the mechanical strength of traditional hydrogels, achieving independent regulation of mechanical strength and cost reduction, and making it suitable for cell culture and controlled drug release.

CN120885144APending Publication Date: 2025-11-04SHANGHAI JIAOTONG UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510893658.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-30
Publication Date
2025-11-04

AI Technical Summary

Technical Problem

Traditional hydrogels adjust mechanical strength by changing the total matrix concentration, which simultaneously alters multiple chemical parameters. This makes it difficult to accurately assess the biological effects of a single mechanical parameter. Furthermore, existing DNA hydrogels are costly to control strength through different sequence designs.

Method used

While keeping the total concentration of DNA monomer building blocks constant, the assembly reaction was carried out under isothermal conditions by adjusting the molar ratio of catalytic initiation strands to DNA monomer building blocks to form DNA hydrogels with different mechanical strengths.

Benefits of technology

It enables independent and convenient control of mechanical strength, independent of variables such as total matrix concentration or stress relaxation rate, reduces costs, and forms DNA hydrogels under normal cell culture conditions, making it suitable for cell biology applications with a wide range of mechanical strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120885144A_ABST
    Figure CN120885144A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of DNA (Deoxyribonucleic Acid) hydrogel with programmable mechanical strength. By regulating and controlling the molar ratio of the catalytic initiating chains to the total amount of the DNA monomer building blocks, multiple hydrogels which are equivalent in mass concentration and have different mechanical strengths are constructed. According to the method, a strategy similar to catalytic assembly is adopted, the feeding molar ratio of a catalytic initiating chain to a DNA monomer building block is creatively adjusted, the proportion of cross-linking reactions at different levels is regulated and controlled, then the DNA hydrogel with different mechanical strengths is synthesized under the isothermal condition, and the storage modulus range is about 200-2000 Pa. In addition, the change of the mechanical strength is independent of the total concentration of the matrix (DNA) of the hydrogel, the DNA sequence, the stress relaxation rate and other properties. The method provides a novel convenient method for constructing DNA hydrogels with different mechanical strengths, and possibly provides a novel tool for researching the specific influence of mechanical properties of materials on cell / tissue behaviors.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the field of DNA nanotechnology, and more particularly relates to a preparation method of a DNA hydrogel with programmable mechanical strength. BACKGROUND

[0002] In recent years, hydrogel materials have shown great potential in a wide range of biomedical application fields such as cell culture and in vitro tissue construction, drug controlled release delivery, tissue repair and regenerative medicine. Among them, the mechanical properties (such as mechanical strength, viscoelasticity, etc.) of hydrogels have a key regulatory role in the behavior of cells such as adhesion, spreading, proliferation, differentiation and even tissue formation. In-depth analysis of the mechanical-biological response mechanism mediated by the mechanical properties of hydrogels not only has important basic research value, but also is the key to promoting its medical applications. However, traditional hydrogel materials (for example, Matrigel matrix gel derived from animal tissues) are often composed of a variety of complex biological molecules. These materials can usually only adjust their macroscopic mechanical strength by changing the total concentration of the matrix. This control method inevitably changes a variety of chemical parameters (such as ligand density, osmotic pressure, etc.) in the hydrogel, thereby introducing multiple variables, making it difficult to precisely separate and evaluate the specific influence of a single mechanical property parameter (such as hardness) on its biological effects.

[0003] DNA molecules have become an excellent material for preparing hydrogels due to their superior biocompatibility and biodegradability. Compared with traditional hydrogel materials, DNA hydrogel components are single and controllable. More importantly, due to the precise base complementary pairing, DNA can precisely prepare microstructures in a programmable manner, thereby regulating the macroscopic physical / chemical / biological properties of the material. Because of the difference in hydrogen bond strength between different base pairs, current studies have used the cross-linking strength between different DNA sequence polymer molecules to synthesize hydrogels with different mechanical strengths while keeping the total concentration of the matrix unchanged. However, this method requires the synthesis of different DNA sequences, resulting in high cost.

[0004] Therefore, it is necessary to develop a DNA hydrogel preparation method with adjustable mechanical strength without the need to synthesize different DNA sequences. SUMMARY

[0005] The purpose of the present application is to provide a preparation method of a DNA hydrogel with programmable mechanical strength, thereby solving the problem that traditional hydrogels change a variety of chemical parameters while adjusting the mechanical strength by changing the total concentration of the matrix, making it difficult to precisely evaluate the biological effects of a single mechanical parameter, and the problem that the existing DNA hydrogel has high cost by designing different sequences to regulate the strength.

[0006] In order to solve the above problems, the technical scheme adopted by the present application is as follows:

[0007] The application provides a preparation method of a mechanically programmable DNA hydrogel, which realizes mechanical strength adjustment of the DNA hydrogel by adjusting a molar ratio of a catalytic initiation chain (I) to total DNA monomer building blocks and performing an assembly reaction under isothermal conditions, while keeping total concentration of the DNA monomer building blocks unchanged, and the preparation method comprises the following steps: 1) providing a solution system comprising at least two DNA monomer building blocks with complementary self-assembly domains and one catalytic initiation chain (I); 2) performing denaturation-renaturation treatment on the DNA monomer building blocks to form preset hairpin structures; 3) mixing the treated DNA monomer building blocks with the catalytic initiation chain in a suitable buffer, and adjusting the molar ratio of the catalytic initiation chain (I) to total DNA monomer building blocks to be between 1:50 and 1:20000; and 4) incubating under isothermal conditions at 30-37 DEG C for 1-5 hours to make the catalytic assembly reaction occur and form DNA hydrogels with different mechanical strengths.

[0008] Preferably, the DNA monomer building blocks comprise first DNA monomer building blocks (H1) and second DNA monomer building blocks (H2).

[0009] Preferably, in step 2), the denaturation-renaturation treatment is that the at least two DNA monomer building blocks are heated to 95 DEG C respectively for 5 minutes, rapidly cooled to an ice bath for 120 minutes to form hairpin structures.

[0010] Preferably, in step 3), the suitable buffer is a PBS buffer or a conventional cell culture medium.

[0011] Preferably, in step 4), the catalytic assembly reaction is performed in a buffer with a pH of 6-8.

[0012] Preferably, in step 4), the isothermal condition is 37 DEG C.

[0013] Preferably, in step 4), the incubation time is 3 hours.

[0014] Preferably, the stress relaxation rate τ1 / 2 of the obtained DNA hydrogel is 1360±50 seconds.

[0015] Preferably, the storage modulus of the obtained DNA hydrogel ranges from 200 Pa to 2000 Pa, and is suitable for cell culture, in-vitro tissue construction or drug controlled release fields.

[0016] It should be understood that the method of the present application is not limited to the DNA sequences used in the examples, and the basic design principles are: 1) the DNA forms different hairpin structures, and the continuous strand displacement reaction between different hairpin structures can form an assembly; 2) the stem and loop sequences of multiple hairpin structures need to strictly avoid cross-reaction to ensure that the cascade reaction is triggered only by a specific initiator; 3) the extension direction of the hairpin structure reaction is three-dimensional. Any person skilled in the art can design DNA sequences according to this principle.

[0017] It should also be understood that in step 1), in addition to using two hairpin structures, three hairpin structures or more hairpin structures can also be used.

[0018] It should be understood that the C-HCR (Clamped Hybridization Chain Reaction) DNA hydrogel uses chemically synthesized DNA assembly, and has a minimum and clear composition. In contrast, traditional animal-derived 3D culture systems, such as Matrigel, have uncertain complex components, batch-to-batch variability, and potential biosafety and ethical issues.

[0019] In this context, the present application proposes a method similar to the strategy of catalytic assembly, which only needs to regulate the molar ratio of three DNA components to synthesize DNA hydrogels with different mechanical strengths under isothermal conditions. Moreover, the change of this mechanical strength is independent of the properties such as the total concentration of the hydrogel matrix and the stress relaxation rate.

[0020] The principle of the present application is described as follows by taking two DNA monomer building blocks (H1 and H2) and one catalytic trigger (I) as an example: the present application designs an isothermal three-dimensional hierarchical organization method similar to catalytic assembly, and assembles DNA into DNA hydrogel with adjustable mechanical strength. Two basic DNA hairpin structures H1 and H2 are used as two metastable monomers for supramolecular copolymerization. The hairpin domains of the two monomers are opened by branch point-mediated hybridization chain reaction under the trigger of trigger I, and the hybridization of complementary sequences is induced in the subsequent copolymerization process. The macro-scale assembly of high-concentration DNA hydrogel is regulated by the steric hindrance of the reaction. Trigger I acts as a “catalytic core” to catalyze the dynamic copolymerization of H1 and H2 around it. Due to the domain restriction formed during the polymerization process, the more catalytic sites I, the smaller the molecular weight of the DNA supramolecules formed by the reaction. These supramolecules act as “DNA building blocks” and further crosslink to form DNA hydrogels with different architectural structures, thereby having adjustable mechanical properties. When the total concentration and sequence of H1 and H2 remain unchanged, the more triggers I, the smaller the primary DNA building blocks formed, resulting in a looser structure of the formed DNA hydrogel. In contrast, reducing the number of I will result in larger DNA building blocks, resulting in a more compact structure of the finally formed DNA hydrogel.

[0021] The DNA hydrogel prepared according to the method of the present application allows independent control of individual components. By adjusting the molar ratio of the catalytic trigger (I) to the total amount of DNA monomer building blocks, the stiffness of the hydrogel can be adjusted in a manner that is almost independent of other variables, such as monomer species, concentration, and stress relaxation of the hydrogel. This can be attributed to the change in the number of triggers (I) resulting in a change in the proportion of different strength crosslinks within the hydrogel. This feature enables us to further study the response of female germ line stem cells (FGSCs) to relatively single mechanical signals. In contrast, traditional methods of adjusting the mechanical properties of the matrix usually change multiple parameters at the same time, such as polymer species and / or concentration, making it difficult to decouple their effects on cell behavior.

[0022] The method for preparing a DNA hydrogel with adjustable mechanical strength provided by the present application has the following advantages compared to the prior art:

[0023] (1) By adjusting the ratio of the catalytic trigger to the monomer building blocks, the mechanical strength is independently and conveniently adjusted, and is independent of variables such as total concentration of the matrix or stress relaxation rate;

[0024] (2) The gelation reaction conditions of the system are mild, and the DNA hydrogel can be formed under normal cell culture conditions (for example, gelation at 37°C in a cell culture medium), which is conducive to cell applications;

[0025] (3) The mechanical strength of the DNA hydrogel can be adjusted in a wide range (storage modulus ~ 200-2000 Pa), and is in the range of the mechanical strength of natural biological soft tissues;

[0026] (4) Different DNA sequences do not need to be synthesized for different strengths, and the operation is convenient and beneficial to reduce the cost.

[0027] In summary, by adjusting the molar ratio of catalytic initiation chain (I) to DNA monomer building block, a plurality of DNA hydrogels with different mechanical strengths and equivalent mass concentrations are constructed. The method uses a similar catalytic assembly strategy, and innovatively adjusts the molar ratio of catalytic initiation chain to DNA monomer building block, adjusts the proportion of different levels of crosslinking reaction, and then synthesizes DNA hydrogels with different mechanical strengths under isothermal conditions, and the storage modulus ranges from about 200 to 2000 Pa. Moreover, the change of the mechanical strength is independent of the total concentration of the matrix (DNA) of the hydrogel, the DNA sequence and the stress relaxation rate. The method provides a new convenient method for constructing DNA hydrogels with different mechanical strengths, and can provide a new tool for studying the specific influence of the mechanical properties of materials on the behavior of cells / tissues. BRIEF DESCRIPTION OF DRAWINGS

[0028] Figure 1 The flow chart for preparing the DNA hydrogel in the application and the schematic diagram for adjusting the mechanical strength are shown in the figure;

[0029] Figure 2 The rheological test results of the DNA hydrogel prepared by using different molar ratios of initiation chain (I) to DNA monomer building block (H1, H2) in the application are shown in the figure;

[0030] Figure 3 The stress relaxation curve of the DNA hydrogel prepared by using different molar ratios of initiation chain (I) to DNA monomer building block (H1, H2) in the application is shown in the figure. DETAILED DESCRIPTION

[0031] The application will be further described below in combination with specific embodiments. It should be understood that the following embodiments are only used to illustrate the application and not to limit the scope of the application. Unless otherwise specified, the technical means used in the embodiments is the conventional operation in the art, or according to the experimental method suggested by the manufacturers of the kits and instrument equipment. The reagents and materials used in the embodiments can be obtained from commercial channels if not otherwise specified.

[0032] Example 1 Preparation of DNA hydrogels with different hardness

[0033] The preparation of DNA hydrogels with different hardness includes the following steps:

[0034] (1) Dissolve three DNA strands H1, H2 and I in phosphate buffer solution (PBS) respectively, the final concentration of H1 is 2 mM, the final concentration of H2 is 4 mM, and the final concentration of I is 100 μM.

[0035] (2) Take H1 (2 mM, 12 μL) and H2 (4 mM, 6 μL) solutions, and add them into different PCR tubes, heat at 95℃ for 5 minutes, and then quickly place on ice for 120 minutes to anneal and form hairpin structures.

[0036] (3) Mix H1 (2 mM, 12 μL) and H2 (4 mM, 6 μL) in the same centrifuge tube in (2), add PBS, and add initiator strand I according to different reaction ratios, if the reaction ratio is 1:100, add initiator strand I (100 μM) at a volume of 2.4 μL, if the reaction ratio is 1:1000, add initiator strand I (100 μM) at a volume of 0.24 μL, and if the reaction ratio is 1:10000, add initiator strand I (10 μM) at a volume of 0.24 μL, so that the total volume of the system is 40 μL, and the final concentration of H1 and H2 remains 600 μM, mix the mixture on a glass sheet, and place it at 37℃ for 3 hours to assemble different DNA hydrogels.

[0037] (4) Prepare 100 μL of DNA hydrogel in (3), and load it on a rheometer to measure the change of its mechanical properties over time. Record the storage modulus and loss modulus under the conditions of a fixed frequency of 1 Hz and a strain of 1%.

[0038] The DNA sequences used in this embodiment 1 are shown in Table 1 below.

[0039] Table 1. DNA sequences

[0040] DNA name DNA sequence (5'-3') I CTAGAGCACAATCACAGGAGCCAG H1 GATCGCGATCCTGGCTCCTGTGATTGTGCTCTAGACATCGCTAGAGCACAATCACAGG H2 CTAGAGCACAATCACAGGAGCCAGTTTTCCTGTGATTGTGCTCTAGCGATGT

[0041] It should be understood that the method of the present application is not limited to the above DNA sequences, which are only used as examples here.

[0042] The design of the DNA monomer building blocks (H1, H2) and the initiator strand (I) follows the following principles:

[0043] 1) The stem of the hairpin structure (H1, H2) forms stable duplex through palindromic sequence, the loop contains specific recognition sequence (e.g. H1 loop contains I's complementary domain CTGGCTCCTGTGATTGTGCTCTAG), ensuring that the strand displacement reaction is only triggered by I; 2) The stem sequence of H1 and H2 is excluded from the possibility of cross-complementarity by BLAST alignment, for example, the H1 stem sequence GATCGCGATC has no >5 bp continuous complementarity with the H2 stem sequence CTAGCGATGT, avoiding non-specific hybridization; 3) The extension direction of the hairpin structure is designed to achieve three-dimensional expansion, such as the 5'-3' sequence of H1 contains a bidirectional hybridization domain (GATCGCGATC), allowing the cascade reaction to extend in multiple dimensions in space.

[0044] As shown in Figure 1 The present application first designs a DNA hydrogel system with adjustable mechanical stiffness, which is modified from the previously described DNA clamped hybridization chain reaction (C-HCR). Briefly, two H1 chains are hybridized to form hairpin duplexes through their palindromic sequences. Two DNA hairpins (H1 duplex and H2) act as metastable monomers in supramolecular copolymerization. The hairpin structure is assembled by annealing. Single-stranded (ss-) DNA (denoted as I) is added to the mixed H1 and H2 hairpin system as a nucleating agent, which can unfold the hairpin motif in H1 through toehold-mediated strand exchange, and then bind to H1 through sequence-specific hybridization. The bound H1 then exposes its ss-binding domain, initiating the unfolding and binding of H2. This in turn triggers another H1, catalyzing the branched polymerization process, and the product extends in three dimensions throughout the reaction, leading to the formation of a DNA hydrogel.

[0045] This type of hydrogel can be regarded as a hierarchical structure involving at least two levels of cross-linking. The first level represents relatively strong cross-linking between monomers through sequence-specific DNA hybridization. The second level refers to weaker cross-linking between the first level structures, which are formed through interactions such as partial base pairing, entanglement and van der Waals forces. In the case of a fixed number of monomers, increasing the number of nucleating agents can promote competitive nucleation in solution, leading to more first-level cross-linking, although its size is limited. The hydrogel formed in this way will contain a larger proportion of weak cross-linking. Conversely, reducing the number of nucleating agents can result in fewer but larger first-level structures, leading to a larger proportion of strong cross-linking in the hydrogel. By adjusting the different reaction ratios to regulate the strength of cross-linking, we can achieve the regulation of the mechanical properties of the hydrogel. Therefore, we expect that by adjusting the ratio of nucleating agents to monomers (I:H1 & H2) in solution, we can achieve the regulation of the mechanical properties of the DNA hydrogel.

[0046] Example 2 Mechanical property test of DNA hydrogel prepared by different molar ratios of initiator (I) to building block (H1, H2)

[0047] In this embodiment, the mechanical properties of different DNA hydrogels were tested by 1% strain, 1 Hz oscillatory shear test while keeping the DNA composition unchanged. The mechanical properties were characterized by storage modulus (G') and loss modulus (G").

[0048] Among them, the storage modulus (G') is a measure of the ability of a material to store energy during periodic deformation. It reflects the elastic part of the material, i.e. the part of the energy that the material can recover after deformation. The loss modulus (G") is a measure of the ability of a material to dissipate energy during periodic deformation. It reflects the viscous part of the material, i.e. the part of the energy that the material cannot recover during deformation. Both the storage modulus (G') and the loss modulus (G") are calculated using industry standard methods, which will not be described here.

[0049] The rheological test results of DNA hydrogels prepared by different molar ratios of initiator (I) to building block (H1, H2) are shown in Figure 2 As can be seen from Figure 2 When the nucleating agent-monomer ratio is gradually adjusted from 1:100 to 1:10000, the storage modulus (G') of each product is about 270 Pa, 315 Pa, 920 Pa and 1130 Pa respectively, and the storage modulus (G') increases significantly with the decrease of the molar ratio of I:(H1, H2).

[0050] As can be seen, under the condition of keeping the DNA composition unchanged, the shear-storage modulus (G') increases significantly with the decrease of the molar ratio of I:(H1, H2), ranging from about 200 Pa to 1200 Pa. The dehydrated DNA hydrogels formed by different ratios have different structural characteristics. With the decrease of the ratio of initiator (I), the size distribution of the hydrogel pores gradually decreases. The average radius of the pores is inversely proportional to the ratio of initiator (I).

[0051] According to the present application, by measuring the storage modulus and the loss modulus, the mechanical properties of the DNA hydrogel under different molar ratios can be evaluated, and the mechanical strength and application characteristics can be optimized.

[0052] Example 3 Stress relaxation rate test of DNA hydrogel prepared by different molar ratios of initiator (I) to building block (H1, H2)

[0053] When the total concentration of H1, H2 is kept at 600 μM, the I concentration is adjusted from 12 μM to 0.06 μM (corresponding to a molar ratio of 1:50 to 1:10000), and the results are as followsFigure 3 As shown, G' = 270 ± 15 Pa at 1:50, pore radius 80 ± 5 nm; G' = 1130 ± 30 Pa at 1:10000, pore radius 30 ± 3 nm; stress relaxation rates are both 1360 ± 80 s, verifying that mechanical strength regulation is independent of stress relaxation characteristics.

[0054] DNA hydrogels obtained from the above different I: (H1, H2) molar ratios, although presenting different mechanical strengths, have a stress relaxation rate that is essentially equivalent (time required for stress to decrease to 1 / 2 is around 1360 s).

[0055] It is noteworthy that these hydrogels, regardless of stiffness, present similar stress relaxation rates (τ1 / 2=~1360 s). Prior to this study we thought that the stress relaxation characteristics of DNA hydrogels were largely dependent on monomer species and concentration, however, according to the present study, the stress relaxation characteristics remain almost constant in these different DNA hydrogels. In contrast, the change in the ratio of the two cross-linking types has little effect on their stress relaxation. Stress relaxation is known to play a crucial role in cell-ECM interactions and biomaterial design for cell culture. Previous studies have suggested that an appropriate stress relaxation rate, which promotes matrix remodeling, is essential to regulate stem cell fate and activity. Here, the stress relaxation rate of the hydrogels prepared according to the present method is comparable to that of native ovarian tissue (τ1 / 2>600 s), and thus can have an impact on the in vitro culture of FGSCs. The results of the present study collectively confirm the establishment of DNA hydrogels with tunable stiffness achieved by precise control of the nucleation of the gelation process. This stiffness regulation is almost independent of monomer species, concentration, and stress relaxation of the hydrogels, allowing us to evaluate the impact of matrix stiffness on cell fate in a decoupled manner.

[0056] The above-described embodiments of the present application are merely intended to illustrate the present application, and are not intended to limit the scope of the present application. Various changes in the above-described embodiments of the present application can be made by those skilled in the art. Any simple, equivalent changes and modifications made in accordance with the contents of the present application application and specification are intended to fall within the scope of the present application. The present application is not limited by the above-described embodiments.

Claims

1. A method for preparing a DNA hydrogel with programmable mechanical strength, characterized in that, While keeping the total concentration of DNA monomer building blocks constant, the mechanical strength of the DNA hydrogel can be adjusted by regulating the molar ratio of the catalytic initiator chain (I) to the total amount of the DNA monomer building blocks under isothermal conditions. The preparation method includes the following steps: 1) Provide a solution system comprising at least two DNA monomer building blocks having complementary self-assembly domains and a catalytic initiation chain (I); 2) The DNA monomer building block is denatured and renatured to form a pre-defined hairpin structure; 3) Mix the treated DNA monomer building blocks with the catalytic initiation strand in a suitable buffer, and adjust the molar ratio of the catalytic initiation strand (I) to the total amount of DNA monomer building blocks to between 1:50 and 1:20000; 4) Incubate at an isothermal temperature of 30~37℃ for 1-5 hours to induce a catalytic assembly reaction and form DNA hydrogels with different mechanical strengths.

2. The preparation method according to claim 1, characterized in that, In step 1), the single-stranded DNA monomer building blocks and the catalytic initiation chain (I) are designed according to the following basic principles: 1) DNA forms different hairpin structures, and different hairpin structures can undergo continuous strand substitution reactions to form assemblies; 2) The stem and loop sequences of multiple hairpin structures must strictly avoid cross-reactions to ensure that the cascade reaction is triggered only by a specific initiator; and 3) The hairpin structure reaction extension direction is three-dimensional.

3. The preparation method according to claim 1, characterized in that, The DNA monomer building blocks include a first DNA monomer building block (H1) and a second DNA monomer building block (H2).

4. The preparation method according to claim 1, characterized in that, In step 2), the denaturation-renaturation process is as follows: at least two DNA monomer building blocks are heated to 95°C and held for 5 minutes, then rapidly cooled to an ice bath and held for 120 minutes to form a hairpin structure.

5. The preparation method according to claim 1, characterized in that, In step 3), the suitable buffer is PBS buffer or conventional cell culture medium.

6. The preparation method according to claim 1, characterized in that, In step 4), the catalytic assembly reaction is carried out in a buffer solution at pH 6-8.

7. The preparation method according to claim 1, characterized in that, In step 4), the isothermal condition is 37°C.

8. The preparation method according to claim 1, characterized in that, In step 4), the incubation time is 3 hours.

9. The preparation method according to claim 1, characterized in that, The stress relaxation rate τ1 / 2 of the obtained DNA hydrogel was 1360±50 seconds.

10. The preparation method according to claim 1, characterized in that, The resulting DNA hydrogel has a storage modulus range of 200~2000 Pa, making it suitable for cell culture, in vitro tissue construction, or controlled drug release.

Citation Information

Cited By

  • DNA hydrogel with kiss hairpin cross-linked structure as well as preparation method and application of DNA hydrogel

    CN121550145A

  • A DNA hydrogel with a kissing hairpin cross-linking structure, its preparation method, and its application.

    CN121550145B